2013
DOI: 10.1371/journal.pone.0062638
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Transporters for Sulfated Steroids in the Human Testis - Cellular Localization, Expression Pattern and Functional Analysis

Abstract: Sulfated steroid hormones are commonly considered to be biologically inactive metabolites, but may be reactivated by the steroid sulfatase into biologically active free steroids, thereby having regulatory function via nuclear androgen and estrogen receptors which are widespread in the testis. However, a prerequisite for this mode of action would be a carrier-mediated import of the hydrophilic steroid sulfate molecules into specific target cells in reproductive tissues such as the testis. In the present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 47 publications
0
46
1
Order By: Relevance
“…8 They are synthesized in steroidogenic tissues or organs, such as the 9 adrenal glands or the gonads, in a series of reactions involving six 10 different cytochromes P450 (CYPs) [1][2][3]. Steroid hormones are 11 categorized into three main classes: the mineralocorticoids and 12 glucocorticoids, regulating the salt and sugar homeostasis, 13 respectively, as well as the sex hormones, which are necessary 14 for the development of the secondary sexual characteristics and for 15 reproduction [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 They are synthesized in steroidogenic tissues or organs, such as the 9 adrenal glands or the gonads, in a series of reactions involving six 10 different cytochromes P450 (CYPs) [1][2][3]. Steroid hormones are 11 categorized into three main classes: the mineralocorticoids and 12 glucocorticoids, regulating the salt and sugar homeostasis, 13 respectively, as well as the sex hormones, which are necessary 14 for the development of the secondary sexual characteristics and for 15 reproduction [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to interact with 25 their corresponding receptors, steroid hormones need to be 26 present in their free and unbound form. Therefore, the conjugation 27 and deconjugation of steroids constitutes a further mechanism 28 that controls the availability of free steroids on a cellular level [9]. Q2 29 The biosynthesis of steroid hormones starts with the side-chain 30 cleavage of cholesterol producing pregnenolone.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the expected presence of the sodium-dependent organic anion transporter (SOAT) in Sertoli cell membranes because sulfated steroids must be transported from Sertoli to germ cells. However, SOAT was recently shown to only localize in germ cells [325]. In other cases, in situ hybridization data have contradicted observations of immunohistochemistry, as noted for cystic fibrosis transmembrane conductance regulator (CFTR), which was localized in Sertoli cell cytoplasm [215,216,326].…”
Section: Mta1mentioning
confidence: 99%
“…13 In addition to the genomic effects of estrogen, rapid nongenomic and membrane-associated responses have finally been recognized as indisputable pathways contributing to estrogen's role in specific cellular functions, including the male reproductive system. 50,[53][54][55][56][57][58][59] ESR1 and ESR2 are involved in rapid, non-genomic transduction effects of estradiol, but the G protein-coupled estrogen receptor-1 (GPER-1) also mediates multiple downstream signaling pathways. [59][60][61][62][63][64][65][66][67] However, this area of investigation has become complicated because some studies have shown an ER antagonist inhibiting GPER-1 activity, 68 while other studies show activation.…”
Section: Source Of Estrogen In the Malementioning
confidence: 99%
“…97 However, it also maintains a capability for ligand-independent activation in the efferent ductule epithelium, possibly working through phosphorylation of the AF-1 domain, 120 or even its membrane receptor. 13,50,[53][54][55][56][57][58][59] Disruption of this ESR1 activity alters the luminal fluid composition, resulting in an alkaline, hypo-osmotic environment that resulted in abnormal sperm morphology. 117,121 Treatment of the Esr1KO sperm with cAMP rescued all defective motility parameters.…”
Section: Source Of Estrogen In the Malementioning
confidence: 99%